Scratch-resistant ultraviolet-proof glass heat insulation film and preparation method thereof
By using the PET base layer, UV insulation layer and scratch-resistant layer structure in the automotive glass insulation film, combined with modified ceria and nano-silicon dioxide, the thermal insulation effect of traditional insulation films is solved. The shortcomings in terms of scratch resistance and ultraviolet protection achieve higher thermal insulation, scratch resistance and ultraviolet resistance.
Patent Information
- Application Number
- CN202411814372.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional automotive glass insulation films have shortcomings in thermal insulation, scratch resistance and ultraviolet protection, and are difficult to meet the high requirements of modern cars for comfort and energy saving.
The glass insulation film consisting of PET base layer, UV-proof insulation layer and scratch-resistant layer is used. The UV-proof insulation layer uses water-based polyurethane emulsion, modified ceria and other additives, and the scratch-resistant layer uses water-based polyurethane emulsion, Aqueous acrylic emulsions, modified nanosilicon dioxide and other additives.
The scratch resistance, UV resistance and heat insulation effect of the glass heat insulation film are significantly improved, while maintaining good optical transparency and visible light transmittance.
Smart Images

Figure BDA0005181372930000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass thermal insulation films and relates to a scratch-resistant and UV-proof glass thermal insulation film and a preparation method thereof. Background Art
[0002] With continued economic growth and people's pursuit of a higher quality of life, the automotive industry is placing increasingly stringent demands on comfort and energy efficiency. Against this backdrop, optimizing the performance of automotive glass, a key factor influencing interior light penetration, passenger comfort, and air conditioning system energy consumption, is crucial. This is especially true during the hot summer months, when intense sunlight shines directly through automotive glass, causing interior temperatures to rise dramatically. This not only accelerates the aging of interior trim and components but also significantly increases the operating burden of the air conditioning system, leading to increased fuel consumption.
[0003] Infrared light in the solar spectrum plays a dominant role in raising vehicle interior temperatures. While ultraviolet light, while a relatively small contributor to total radiant energy, contributes significantly to human skin damage and accelerates the degradation of interior materials. Ideal automotive glass should effectively block ultraviolet light and most infrared light while maintaining good visible light transmittance, balancing interior lighting requirements with thermal insulation performance to enhance driving comfort and reduce energy consumption and emissions. However, conventional automotive glass thermal films still have performance limitations, such as limited insulation, susceptibility to scratching, and insufficient UV protection. Therefore, developing a glass thermal film that is both scratch-resistant and provides effective UV protection while also possessing excellent thermal insulation properties is crucial. Summary of the Invention
[0004] The present invention aims to provide a scratch-resistant and UV-proof glass heat-insulating film and a preparation method thereof, which has the characteristics of scratch resistance, UV resistance and heat insulation.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A scratch-resistant and UV-proof glass insulation film, comprising, from the inside out, a PET base layer, an anti-UV insulation layer, and a scratch-resistant layer, wherein the anti-UV insulation layer has the following formula: in parts by weight: 90-100 parts of aqueous polyurethane emulsion, 15-20 parts of modified cerium dioxide, 5-7 parts of film-forming agent, 3-5 parts of leveling agent, and 2-3 parts of defoaming agent.
[0007] The formula of the scratch-resistant layer is as follows: in parts by weight, 70-80 parts of water-based polyurethane emulsion, 10-20 parts of water-based acrylic emulsion, 10-15 parts of modified nano-silica, 4-6 parts of film-forming agent, 2-3 parts of leveling agent, 1-2 parts of defoaming agent,
[0008] The preparation method of modified cerium dioxide is as follows:
[0009] S1-1: 5-10 parts by weight of cerium nitrate were added to 80-90 parts by weight of anhydrous ethanol, and ultrasonicated at 40°C for 30 minutes. Ammonia water was added dropwise while stirring at a speed of 700-800 r / min until the solution had a pH of 4-6. The mixture was stirred at 50°C for 1 hour, and then transferred to a reactor at a constant temperature of 170°C for 12 hours. The mixture was washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours. The mixture was then ball-milled for 2 hours at a speed of 150 r / min to obtain powder A.
[0010] S1-2: 2-3 parts by weight of silicic acid and 25-35 parts by weight of glycerol were mixed, ultrasonicated for 10 minutes, and 1-1.5 parts by weight of sodium borohydride were added under stirring at 500-600 rpm. Stirring was continued at 50°C for 20 minutes, followed by microwave irradiation. The mixture was filtered and the filtrate was dialyzed using a dialysis bag for 6 hours. The mixture was then freeze-dried in a freeze dryer at -30°C for 6 hours to obtain powder B.
[0011] S1-3: Mix 2 to 3 parts by weight of powder B and 20 to 30 parts by weight of deionized water, ultrasonicate for 20 to 30 minutes, add 8 to 12 parts by weight of powder A, stir at 60°C for 1 to 2 hours, then add 0.5 to 1 part by weight of γ-aminopropyltriethoxysilane, continue stirring for 30 minutes, wash with deionized water and place in a vacuum oven at 60°C to dry for 6 hours to obtain the modified cerium dioxide.
[0012] Furthermore, the dropping speed of the ammonia water in S1-1 is 0.5 mL / min.
[0013] Furthermore, in said S1-2, the power of the microwave irradiation is 800-900W, the time of the microwave irradiation is 5-15 minutes, and the temperature of the microwave irradiation is 150-200°C.
[0014] Furthermore, the film-forming aid is alcohol ester-12.
[0015] Furthermore, the leveling agent is one or more of BYK375, Tego410, and Tego450.
[0016] Furthermore, the defoaming agent is one or more of BYK021, BYK022, and BYK023.
[0017] Furthermore, the preparation method of the modified nano-silica is as follows:
[0018] 10 to 20 parts by weight of nano-silica are placed in a mixture of 50 to 60 parts by weight of ethanol and acetone, and ultrasonicated for 30 minutes. 5 to 10 parts by weight of polytetrafluoroethylene emulsion and 3 to 5 parts by weight of polyvinyl alcohol are added, and ultrasonic dispersion is continued for 30 minutes. The mixture is then rotary evaporated at 50° C. for 2 hours, washed with deionized water, dried in a vacuum drying oven for 6 hours, ball-milled in a ball mill for 2 hours, and passed through a 500-mesh sieve to obtain the modified nano-silica.
[0019] Furthermore, the mass ratio of ethanol to acetone in the mixture of ethanol and acetone is 2:1.
[0020] Furthermore, the ball milling speed is 300 r / min.
[0021] A method for preparing a scratch-resistant and UV-proof glass insulation film, the specific steps of the preparation method are as follows:
[0022] S10-1: According to the formula of the anti-ultraviolet heat-insulating layer, a water-based polyurethane emulsion, modified cerium dioxide, a film-forming agent, a leveling agent, and a defoamer were mixed and stirred for 1 hour at a stirring speed of 150 to 250 r / min to obtain coating B. Coating B was applied to the PET substrate at a coating line speed of 15 to 20 m / s to a coating thickness of 10 μm. The coating was then dried at 50°C for 40 to 60 min to obtain the anti-ultraviolet heat-insulating layer.
[0023] S10-2: According to the formula of the scratch-resistant layer, the aqueous polyurethane emulsion, aqueous acrylic emulsion, modified nano-silica, film-forming agent, leveling agent and defoaming agent are mixed and stirred for 1 hour at a stirring speed of 150 to 250 r / min to obtain coating C. The coating C is applied on the anti-ultraviolet and heat-insulating layer at a coating line speed of 20 to 30 m / s and a coating thickness of 5 μm. The coating is dried at 50°C for 30 to 50 minutes to obtain the scratch-resistant and anti-ultraviolet glass insulation film.
[0024] The band gap of nano-cerium dioxide reaches 3.15eV, indicating that it has good absorption properties for ultraviolet light, while almost no absorption of the visible light portion of sunlight, thus ensuring good optical transparency. Compared with ultraviolet shielding materials such as titanium dioxide and zinc oxide, the photocatalytic properties of ceria are weaker, so it is not easy to cause oxidative damage to the organic components in the film, effectively extending the service life of the thermal insulation film. To further improve the ultraviolet light shielding efficiency of nano-cerium dioxide, silicon quantum dots with unique physical and chemical properties are introduced as dopants. Silicon quantum dots exhibit strong absorption capacity in the ultraviolet light region. Therefore, combining them with nano-cerium dioxide can enhance the ultraviolet light absorption performance of the composite material. When silicon quantum dots are doped onto nano-cerium dioxide, they introduce additional defects into the ceria matrix. These defects not only act as absorption centers for ultraviolet light, effectively increasing the area and efficiency of light absorption, but also promote the interaction between silicon quantum dots and ceria in processes such as charge transfer and energy transfer, thereby promoting the absorption and conversion of ultraviolet light by the modified ceria, thereby further improving the anti-ultraviolet performance of the composite material. In addition, ceria is also a good thermal insulation material. The oxygen vacancies and defects in its crystal structure can scatter and hinder heat conduction. When silicon quantum dots are doped into ceria, these silicon quantum dots introduce additional interfaces and scattering centers into the material, further hindering the heat conduction process and improving the thermal insulation performance of the material. Because cerium dioxide has a large specific surface area and high specific surface energy, it is difficult to disperse in non-polar media and easily agglomerates in polar media. Therefore, γ-aminopropyltriethoxysilane is introduced for surface modification, which effectively enhances the connection between silicon quantum dot-doped cerium dioxide and aqueous polyurethane emulsion, avoids local agglomeration, and effectively improves the stability and dispersibility of the modified cerium dioxide.
[0025] Nano-silica has the characteristics of high hardness and good wear resistance. It can fill the tiny pores and defects on the surface of glass insulation film, forming a smoother and denser surface structure, which helps to effectively improve the wear resistance of the film. At the same time, nano-silica also has excellent ultraviolet reflection and scattering capabilities, which can effectively reduce the destructive effects of ultraviolet rays on the insulation film. Polytetrafluoroethylene is a material with a low friction coefficient, low surface energy, and low density. Combining it with nano-silica can significantly improve the wear resistance and scratch resistance of the film due to the lubricity and wear resistance of polytetrafluoroethylene, which can effectively reduce the damage to the glass film caused by external friction. At the same time, the fluorine atoms in polytetrafluoroethylene have excellent chemical stability and can resist corrosion from various chemicals, thereby extending the service life of the insulation film. Polyvinyl alcohol, as a polymer compound, can form a certain barrier effect between modified nano-silica, effectively improving the dispersibility and stability of modified nano-silica in water-based polyurethane emulsions, inhibiting its agglomeration, and achieving a more uniform distribution in the film. In addition, polyvinyl alcohol has good bonding and adhesion properties, which can enhance the bonding between the modified nano-silica and the substrate. The high specific surface area and excellent thermal stability of the modified nano-silica can also make it an effective thermal insulation filler, further improving the thermal insulation performance of the thermal insulation film.
[0026] Beneficial effects of the present invention:
[0027] (1) The combination of nano-cerium dioxide and silicon quantum dots significantly enhances the ultraviolet light absorption performance while maintaining good optical transparency. The thermal insulation properties of cerium dioxide itself and the additional scattering centers introduced by silicon quantum dots further hinder heat conduction and improve the thermal insulation effect of the material. In addition, the surface modification with γ-aminopropyltriethoxysilane effectively enhances the stability and dispersibility of the composite material in aqueous polyurethane emulsion, avoiding local agglomeration.
[0028] (2) The combination of nano-silica and polytetrafluoroethylene significantly improves the wear resistance and scratch resistance of the film while maintaining good UV protection. The addition of polyvinyl alcohol effectively improves the dispersibility and stability of modified nano-silica in the film and enhances its bonding with the substrate. In addition, the high specific surface area and thermal stability of modified silica further improve the thermal insulation performance of the thermal insulation film. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] In the Examples of the present invention and the Comparative Examples:
[0031] Waterborne polyurethane emulsion: purchased from Dongguan Xuhua New Material Technology Co., Ltd.
[0032] Water-based acrylic emulsion: purchased from Changzhou Zemu Water-based Material Technology Co., Ltd.
[0033] Cerium nitrate: purchased from Shandong Zhengxing New Materials Co., Ltd.
[0034] Anhydrous ethanol: purchased from Xi'an Sanpu Chemical Reagent Co., Ltd.
[0035] Ammonia: purchased from Changzhou Chengyi Biotechnology Co., Ltd.
[0036] Silicic acid: purchased from Guangdong Qianjin Chemical Reagent Co., Ltd.
[0037] Glycerol: purchased from Taishan Changshun Glycerol Products Co., Ltd.
[0038] γ-Aminopropyltriethoxysilane: purchased from Jiangsu Yangtze River Tianyue New Materials Co., Ltd.
[0039] Nano-silica: purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0040] Polytetrafluoroethylene emulsion: purchased from Shanghai Xige Biotechnology Co., Ltd.;
[0041] Polyvinyl alcohol: purchased from Shanxi Sanwei Shengtai New Material Technology Co., Ltd.
[0042] Alcohol ester-12: purchased from Shanghai Biyang Industrial Co., Ltd.;
[0043] Tego410 and Tego450 were purchased from Shanghai Buding Chemical Co., Ltd.
[0044] BYK021, BYK022, BYK023, BYK375: purchased from Guangzhou Ligou New Materials Co., Ltd.
[0045] PET base film: purchased from Dongchang Group Co., Ltd.
[0046] Example 1
[0047] A scratch-resistant and UV-proof glass insulation film, comprising a PET base layer, an anti-UV insulation layer, and a scratch-resistant layer from the inside out, wherein the formula 1 of the anti-UV insulation layer is as follows: in parts by weight, 95 parts of aqueous polyurethane emulsion, 17 parts of modified cerium dioxide, 126 parts of alcohol ester, 754 parts of BYK3, and 12.5 parts of BYK02.
[0048] The formula 1 of the scratch-resistant layer is as follows: in parts by weight, 75 parts of aqueous polyurethane emulsion, 15 parts of aqueous acrylic emulsion, 12 parts of modified nano-silica, 125 parts of alcohol ester, 2.5 parts of BYK375, 11.5 parts of BYK02,
[0049] The preparation method of modified cerium dioxide is as follows:
[0050] S1-1: 7 parts by weight of cerium nitrate were added to 85 parts by weight of anhydrous ethanol, and ultrasonicated at 40°C for 30 min. Ammonia water was added dropwise at a rate of 0.5 mL / min while stirring at a speed of 750 r / min until the solution had a pH of 5. The mixture was stirred at 50°C for 1 h. The mixture was then transferred to a reactor and kept at a constant temperature of 170°C for 12 h. The mixture was washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 h. The mixture was then ball milled for 2 h at a speed of 150 r / min to obtain powder A.
[0051] S1-2: 2.5 parts by weight of silicic acid and 30 parts by weight of glycerol were mixed, ultrasonicated for 10 minutes, and 1.2 parts by weight of sodium borohydride was added under stirring at 550 rpm. The mixture was stirred at 50°C for 20 minutes, and then microwaved at a power of 850 W, a time of 10 minutes, and a temperature of 170°C. The mixture was filtered and the filtrate was dialyzed with a dialysis bag for 6 hours. The mixture was then freeze-dried in a freeze dryer at -30°C for 6 hours to obtain powder B.
[0052] S1-3: Mix 2.5 parts by weight of powder B and 25 parts by weight of deionized water, ultrasonicate for 25 minutes, add 10 parts by weight of powder A, stir at 60°C for 1.5 hours, then add 0.7 parts by weight of γ-aminopropyltriethoxysilane, continue stirring for 30 minutes, wash with deionized water and place in a vacuum oven at 60°C to dry for 6 hours to obtain the modified cerium dioxide.
[0053] The preparation method of the modified nano-silica is as follows:
[0054] 15 parts by weight of nano-silica was placed in a mixture of 55 parts by weight of ethanol and acetone, wherein the mass ratio of ethanol to acetone in the mixture was 2:1, and ultrasonic treatment was performed for 30 minutes. 8 parts by weight of polytetrafluoroethylene emulsion and 4 parts by weight of polyvinyl alcohol were added, and ultrasonic dispersion was continued for 30 minutes. The mixture was then rotary evaporated at 50° C. for 2 hours, washed with deionized water, dried in a vacuum drying oven for 6 hours, and ball-milled in a ball mill for 2 hours at a ball mill speed of 300 r / min. The mixture was sieved through a 500-mesh screen to obtain the modified nano-silica.
[0055] A method for preparing a scratch-resistant and UV-proof glass insulation film, the specific steps of the preparation method are as follows:
[0056] S10-1: According to Recipe 1 for the UV protection and heat insulation layer, a water-based polyurethane emulsion, modified cerium dioxide, alcohol ester-12, BYK375, and BYK021 were mixed and stirred for 1 hour at a stirring speed of 200 r / min to obtain coating B. Coating B was applied to the PET substrate at a coating line speed of 18 m / s to a coating thickness of 10 μm. The coating was then dried at 50°C for 50 min to obtain the UV protection and heat insulation layer.
[0057] S10-2: According to the formula 1 of the scratch-resistant layer, the aqueous polyurethane emulsion, the aqueous acrylic emulsion, the modified nano-silica, the alcohol ester-12, BYK375 and BYK021 were mixed and stirred for 1 hour at a stirring speed of 200 r / min to obtain coating C. The coating C was applied on the anti-ultraviolet and heat-insulating layer at a coating line speed of 25 m / s and a coating thickness of 5 μm. The coating was dried at 50°C for 40 minutes to obtain the scratch-resistant and anti-ultraviolet glass insulation film.
[0058] Example 2
[0059] A scratch-resistant and UV-proof glass insulation film, comprising a PET base layer, an anti-UV insulation layer, and a scratch-resistant layer from the inside out. The formula 2 of the anti-UV insulation layer is as follows: in parts by weight: 90 parts of aqueous polyurethane emulsion, 15 parts of modified cerium dioxide, 125 parts of alcohol ester, 103 parts of Tego 4, and 222 parts of BYK 02.
[0060] The formula 2 of the scratch-resistant layer is as follows: in parts by weight, 70 parts of aqueous polyurethane emulsion, 10 parts of aqueous acrylic emulsion, 10 parts of modified nano-silica, 124 parts of alcohol ester, 2 parts of Tego 410, 21 parts of BYK 022,
[0061] The preparation method of modified cerium dioxide is as follows:
[0062] S1-1: 5 parts by weight of cerium nitrate were added to 80 parts by weight of anhydrous ethanol, and ultrasonicated at 40°C for 30 min. Ammonia water was added dropwise at a rate of 0.5 mL / min with stirring at a speed of 700 r / min until the solution had a pH of 4. The mixture was stirred at 50°C for 1 h. The mixture was then transferred to a reactor and kept at a constant temperature of 170°C for 12 h. The mixture was washed with deionized water and anhydrous ethanol, dried in a vacuum drying oven at 60°C for 12 h, and then ball-milled in a ball mill at a speed of 150 r / min for 2 h to obtain powder A.
[0063] S1-2: 2 parts by weight of silicic acid and 25 parts by weight of glycerol were mixed, ultrasonicated for 10 minutes, and 1 part by weight of sodium borohydride was added under stirring at 500 rpm. Stirring was continued at 50°C for 20 minutes, followed by microwave irradiation at a power of 800 W, a time of 5 minutes, and a temperature of 150°C. The mixture was filtered and the filtrate was dialyzed with a dialysis bag for 6 hours, and freeze-dried in a freeze dryer at -30°C for 6 hours to obtain powder B;
[0064] S1-3: Mix 2 parts by weight of powder B and 20 parts by weight of deionized water, ultrasonicate for 20 minutes, add 8 parts by weight of powder A, stir at 60°C for 1 hour, then add 0.5 parts by weight of γ-aminopropyltriethoxysilane, continue stirring for 30 minutes, wash with deionized water and place in a vacuum oven at 60°C to dry for 6 hours to obtain the modified cerium dioxide.
[0065] The preparation method of the modified nano-silica is as follows:
[0066] 10 parts by weight of nano-silica was placed in a mixture of 50 parts by weight of ethanol and acetone, wherein the mass ratio of ethanol to acetone in the mixture was 2:1, and ultrasonic treatment was performed for 30 minutes. 5 parts by weight of polytetrafluoroethylene emulsion and 3 parts by weight of polyvinyl alcohol were added, and ultrasonic dispersion was continued for 30 minutes. The mixture was then rotary evaporated at 50° C. for 2 hours, washed with deionized water, dried in a vacuum drying oven for 6 hours, and ball-milled in a ball mill for 2 hours at a ball mill speed of 300 r / min. The mixture was sieved through a 500-mesh screen to obtain the modified nano-silica.
[0067] A method for preparing a scratch-resistant and UV-proof glass insulation film, the specific steps of the preparation method are as follows:
[0068] S10-1: According to Formula 2 for the UV protection and heat insulation layer, a water-based polyurethane emulsion, modified cerium dioxide, alcohol ester-12, Tego 410, and BYK 022 were mixed and stirred for 1 hour at a stirring speed of 150 r / min to obtain coating B. Coating B was applied to the PET substrate at a coating line speed of 15 m / s to a coating thickness of 10 μm. The coating was then dried at 50°C for 40 min to obtain the UV protection and heat insulation layer.
[0069] S10-2: According to the formula 2 of the scratch-resistant layer, the aqueous polyurethane emulsion, the aqueous acrylic emulsion, the modified nano-silica, the alcohol ester-12, the Tego410 and the BYK022 were mixed and stirred for 1 hour at a stirring speed of 150 r / min to obtain the coating C. The coating C was applied on the anti-ultraviolet and heat-insulating layer at a coating line speed of 20 m / s and a coating thickness of 5 μm. The coating was dried at 50°C for 30 minutes to obtain the scratch-resistant and anti-ultraviolet glass insulation film.
[0070] Example 3
[0071] A scratch-resistant and UV-proof glass insulation film, comprising a PET base layer, an anti-UV insulation layer, and a scratch-resistant layer from the inside out. The formula 3 of the anti-UV insulation layer is as follows: in parts by weight: 100 parts of aqueous polyurethane emulsion, 20 parts of modified cerium dioxide, 127 parts of alcohol ester, 5 parts of Tego 450, and 33 parts of BYK023.
[0072] The formula 3 of the scratch-resistant layer is as follows: in parts by weight, 80 parts of aqueous polyurethane emulsion, 20 parts of aqueous acrylic emulsion, 15 parts of modified nano-silica, 126 parts of alcohol ester, 3 parts of Tego450, 32 parts of BYK02,
[0073] The preparation method of modified cerium dioxide is as follows:
[0074] S1-1: 10 parts by weight of cerium nitrate were added to 90 parts by weight of anhydrous ethanol, and ultrasonicated at 40°C for 30 min. Ammonia water was added dropwise at a rate of 0.5 mL / min with stirring at a speed of 800 r / min until the solution had a pH of 6. The mixture was stirred at 50°C for 1 h. The mixture was then transferred to a reactor and kept at 170°C for 12 h. The mixture was washed with deionized water and anhydrous ethanol, dried in a vacuum drying oven at 60°C for 12 h, and then ball-milled for 2 h at a speed of 150 r / min to obtain powder A.
[0075] S1-2: 3 parts by weight of silicic acid and 35 parts by weight of glycerol were mixed and ultrasonicated for 10 minutes. 1.5 parts by weight of sodium borohydride was added under stirring at 600 rpm, and stirring was continued at 50°C for 20 minutes. The mixture was then irradiated with microwaves at a power of 900 W, a time of 15 minutes, and a temperature of 200°C. The mixture was filtered and the filtrate was dialyzed with a dialysis bag for 6 hours. The mixture was then freeze-dried in a freeze dryer at -30°C for 6 hours to obtain powder B.
[0076] S1-3: Mix 3 parts by weight of powder B and 30 parts by weight of deionized water, ultrasonicate for 30 minutes, add 12 parts by weight of powder A, stir at 60°C for 2 hours, then add 1 part by weight of γ-aminopropyltriethoxysilane, continue stirring for 30 minutes, wash with deionized water and place in a vacuum oven at 60°C to dry for 6 hours to obtain the modified cerium dioxide.
[0077] The preparation method of the modified nano-silica is as follows:
[0078] 20 parts by weight of nano-silica are placed in a mixture of 60 parts by weight of ethanol and acetone, wherein the mass ratio of ethanol to acetone in the mixture of ethanol and acetone is 2:1, and ultrasonic treatment is performed for 30 minutes. 10 parts by weight of polytetrafluoroethylene emulsion and 5 parts by weight of polyvinyl alcohol are added, and ultrasonic dispersion is continued for 30 minutes. The mixture is then rotary evaporated at 50° C. for 2 hours, washed with deionized water, dried in a vacuum drying oven for 6 hours, and ball-milled in a ball mill for 2 hours at a ball mill speed of 300 r / min. The mixture is sieved through a 500-mesh screen to obtain the modified nano-silica.
[0079] A method for preparing a scratch-resistant and UV-proof glass insulation film, the specific steps of the preparation method are as follows:
[0080] S10-1: According to Formula 3 for the UV protection and heat insulation layer, a water-based polyurethane emulsion, modified cerium dioxide, alcohol ester-12, Tego 450, and BYK 023 were mixed and stirred for 1 hour at a stirring speed of 250 r / min to obtain coating B. Coating B was applied to the PET substrate at a coating line speed of 20 m / s to a coating thickness of 10 μm. The coating was then dried at 50°C for 60 min to obtain the UV protection and heat insulation layer.
[0081] S10-2: According to the formula 3 of the scratch-resistant layer, the aqueous polyurethane emulsion, the aqueous acrylic emulsion, the modified nano-silica, the alcohol ester-12, the Tego450 and the BYK023 were mixed and stirred for 1 hour at a stirring speed of 250 r / min to obtain the coating C. The coating C was applied on the UV protection and heat insulation layer at a coating line speed of 30 m / s and a coating thickness of 5 μm. The coating was dried at 50°C for 50 min to obtain the scratch-resistant and UV protection glass insulation film.
[0082] Comparative Example 1
[0083] The cerium dioxide was not modified, and the remaining steps were the same as those in Example 1.
[0084] Comparative Example 2
[0085] The nano-silica was not modified, and the remaining steps were the same as in Example 1.
[0086] Abrasion resistance test: According to GB 31849-2015 automotive film glass standard, the haze caused by abrasion of the films prepared in Example and Comparative Example was tested respectively;
[0087] Light transmittance test: The ultraviolet light blocking rate, visible light transmittance, and infrared blocking rate of the automobile glass films prepared in the examples and comparative examples were tested according to GB 31849-2015 automobile film glass standard.
[0088] The experimental data are recorded in the following table:
[0089]
[0090]
[0091] It can be seen from the data of the embodiments and comparative examples that the anti-UV heat-insulating layer is prepared by using cerium dioxide synergistically modified with silicon quantum dots and γ-aminopropyltriethoxysilane, and the scratch-resistant layer is prepared by using nano-silica synergistically modified with polytetrafluoroethylene and polyvinyl alcohol, which significantly improves the scratch-resistant and anti-UV glass insulation film and has good visible light transmittance and scratch resistance, UV resistance and heat insulation properties.
[0092] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A scratch-resistant and UV-proof glass thermal insulation film, characterized in that: The glass thermal insulation film comprises a PET base layer, an anti-ultraviolet thermal insulation layer and a scratch-resistant layer from the inside to the outside, wherein the formula of the anti-ultraviolet thermal insulation layer is as follows: in parts by weight, 90 to 100 parts of aqueous polyurethane emulsion, 15 to 20 parts of modified cerium dioxide, 5 to 7 parts of film-forming agent, 3 to 5 parts of leveling agent, and 2 to 3 parts of defoaming agent. The formula of the scratch-resistant layer is as follows: by weight, 70-80 parts of waterborne polyurethane emulsion, 10-20 parts of waterborne acrylic emulsion, 10-15 parts of modified nano-silicon dioxide, 4-6 parts of film-forming agent, 2-3 parts of leveling agent, 1-2 parts of defoaming agent, Wherein, the preparation method of modified cerium dioxide is as follows: S1-1: 5-10 parts by weight of cerium nitrate are added to 80-90 parts by weight of anhydrous ethanol, ultrasonicated at 40°C for 30 minutes, and ammonia water is added dropwise to a solution pH of 4-6 under stirring conditions at a speed of 700-800 r / min, stirred at 50°C for 1 hour, and then transferred to a reactor at a constant temperature of 170°C for 12 hours, washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours, and then ball-milled in a ball mill for 2 hours at a ball mill speed of 150 r / min to obtain powder A; S1-2: 2-3 parts by weight of silicic acid and 25-35 parts by weight of propylene glycol were mixed, ultrasonicated for 10 min, 1-1.5 parts by weight of sodium borohydride were added under stirring conditions of 500-600 r / min, and stirring was continued at 50° C. for 20 min, followed by microwave irradiation, filtration, and the filtrate was dialyzed with a dialysis bag for 6 h, and freeze-dried in a freeze dryer at -30° C. for 6 h to obtain powder B; S1-3: Mix 2 to 3 parts by weight of powder B and 20 to 30 parts by weight of deionized water, ultrasonicate for 20 to 30 minutes, add 8 to 12 parts by weight of powder A, stir at 60°C for 1 to 2 hours, then add 0.5 to 1 part by weight of γ-aminopropyltriethoxysilane, continue stirring for 30 minutes, wash with deionized water and place in a vacuum oven at 60°C to dry for 6 hours to obtain the modified cerium dioxide.
2. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: The dropping speed of the ammonia water in the S1-1 is 0.5 mL / min.
3. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: In the S1-2, the power of the microwave irradiation is 800-900W, the time of the microwave irradiation is 5-15min, and the temperature of the microwave irradiation is 150-200°C.
4. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: The film-forming aid is alcohol ester-12.
5. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: The leveling agent is one or more of BYK375, Tego410, and Tego450.
6. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: The defoaming agent is one or more of BYK021, BYK022 and BYK023.
7. The scratch-resistant and UV-proof glass thermal insulation film according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is as follows: 10 to 20 parts by weight of nano-silicon dioxide are placed in a mixture of 50 to 60 parts by weight of ethanol and acetone, and ultrasonicated for 30 minutes. 5 to 10 parts by weight of polytetrafluoroethylene emulsion and 3 to 5 parts by weight of polyvinyl alcohol are added, and ultrasonic dispersion is continued for 30 minutes. Then, rotary evaporation is performed at 50° C. for 2 hours, and the mixture is washed with deionized water. The mixture is placed in a vacuum drying oven for 6 hours, placed in a ball mill for 2 hours, and passed through a 500-mesh sieve to obtain the modified nano-silicon dioxide.
8. The scratch-resistant and UV-proof glass thermal insulation film according to claim 7, characterized in that: The mass ratio of ethanol to acetone in the mixed solution of ethanol and acetone is 2:
1.
9. The scratch-resistant and UV-proof glass thermal insulation film according to claim 7, characterized in that: The ball mill speed is 300r / min.
10. A method for preparing the scratch-resistant and UV-proof glass thermal insulation film according to claims 1 to 9, characterized in that: The specific steps of the preparation method are as follows: S10-1: According to the formula of the anti-ultraviolet heat-insulating layer, the aqueous polyurethane emulsion, modified cerium dioxide, film-forming agent, leveling agent and defoaming agent are mixed and stirred for 1 hour at a stirring speed of 150 to 250 r / min to obtain coating B, and the coating B is coated on the PET substrate layer at a coating line speed of 15 to 20 m / s and a coating thickness of 10 μm, and dried at 50° C. for 40 to 60 min to obtain the anti-ultraviolet heat-insulating layer; S10-2: According to the formula of the scratch-resistant layer, the aqueous polyurethane emulsion, the aqueous acrylic emulsion, the modified nano-silica, the film-forming agent, the leveling agent and the defoaming agent are mixed and stirred for 1 hour at a stirring speed of 150 to 250 r / min to obtain coating C. The coating C is applied on the anti-ultraviolet and heat-insulating layer at a coating speed of 20 to 30 m / s and a coating thickness of 5 μm. The coating is dried at 50°C for 30 to 50 min to obtain the scratch-resistant and anti-ultraviolet glass insulation film.
Citation Information
Patent Citations
Sun-proof heat-insulating automobile film and preparation method therefor
CN105111483A
Anti-ultraviolet glass film and manufacturing method thereof
CN105199617A
Heat-insulation anti-ultraviolet automobile membrane and preparation method thereof
CN105348750A
Scratch-resistant outdoor powder paint
CN106366892A
Anti-ultraviolet automobile glass film and preparation method thereof
CN118308021A